2002
DOI: 10.1542/peds.109.4.e60
|View full text |Cite
|
Sign up to set email alerts
|

Zidovudine and Perinatal Human Immunodeficiency Virus Type 1 Transmission: A Population-Based Approach

Abstract: ABSTRACT.Objective. This study examined the impact of the full 3-arm zidovudine regimen on the perinatal transmission of human immunodeficiency virus type 1 (HIV-1) using population-based data.Methods. We retrospectively ascertained information on zidovudine prescription and other characteristics of HIV-infected pregnant women and children for birth cohort years 1993, 1995, 1996, and 1997 using HIV/ acquired immunodeficiency syndrome registry data from a state health department supplemented by medical record r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Maternal-fetal human immunodeficiency virus-1 (HIV-1) transmission has decreased rapidly during the past 10 years, largely due to nucleoside reverse transcriptase inhibitor (NRTI) therapy given during pregnancy and delivery [Harris et al, 2002;Cooper et al, 1996]. Zidovudine (AZT), the first NRTI recommended for this purpose, is now a frequent component of typical combination protocols that include two NRTIs and either a non-NRTI or a protease inhibitor [''Guidelines,'' 2005a;''Guidelines,'' Invited article on the genotoxicity of perinatal NRTI therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal-fetal human immunodeficiency virus-1 (HIV-1) transmission has decreased rapidly during the past 10 years, largely due to nucleoside reverse transcriptase inhibitor (NRTI) therapy given during pregnancy and delivery [Harris et al, 2002;Cooper et al, 1996]. Zidovudine (AZT), the first NRTI recommended for this purpose, is now a frequent component of typical combination protocols that include two NRTIs and either a non-NRTI or a protease inhibitor [''Guidelines,'' 2005a;''Guidelines,'' Invited article on the genotoxicity of perinatal NRTI therapy.…”
Section: Introductionmentioning
confidence: 99%
“…No suministro de ZDV mediante el protocolo PACTG 076. 33 Los procedimientos diagnósticos prenatales "invasivos" están contraindicados, tales como amniocentesis, cordocentesis y biopsia de vellosidad corial.…”
Section: Control Prenatal De La Gestante Infectada Con Vih 19-25unclassified
“…The second phase, spanning 1994 to 1996, followed publication of the results of Pediatric AIDS Clinical Trials Group protocol 076, demonstrating the efficacy of zidovudine prophylaxis in preventing transmission 3 ; during this period there was rapid and widespread implementation of the PACTG 076 antepartum/intrapartum/infant zidovudine prophylaxis regimen throughout the United States and other resource-rich countries, and decreases in MTCT rates to approximately 5% to 8% were observed by as early as 1995. [4][5][6] The third phase began around 1997, when combination antiretroviral regimens (primarily dual nucleoside analogue therapy) became more widely used by pregnant women, with a further decrease in MTCT rates to 3% to 4%. 7 The current phase began around 1999, when highly active antiretroviral therapy began to be more widely prescribed to pregnant women, and several studies were published that indicated that elective cesarean delivery reduced the risk of transmission 8,9 ; in 2001, highly active antiretroviral therapy and elective cesarean delivery were recommended by the US Public Health Service Task Force for all HIV-1-infected pregnant women with HIV-1 RNA levels greater than 1000 copies/mL.…”
Section: Successes and Challengesmentioning
confidence: 99%